Epoch-Making Changes in the Cultural Evolution of Communication: Communication Technologies Seen as Organized Hubs of Skillful Human Activities - Kivinen Osmo; Piiroinen Tero (John Wiley & Sons Ltd., 2022)
This paper applies methodological relationalism, leaning on a pragmatist theory of action of classical Deweyan origin, supplemented among other things with Alva Noë's enactivism, to analyze the development of communication technologies as a part of human cultural evolution. Tool-use and technologies are understood as skillful human activities that form hubs of organized activity in developed human communities. Appreciating the quite slow pace of evolution, the article adopts, all told, a two million year time frame. Six epochs of cultural evolution are distinguished, linked to the introduction of communication tools and technologies as skillful human activities that serve the members of growing communities in the ecological niche at hand. The first two epochs arose from forms of communication serving local, small-sized hunter-gatherer bands; the second couple arose with technologies apt for building nation-wide communities and culture; and the latest two have been propelled by global communication networks, having an impact on billions of people. Finally, certain peculiarities of the presently unfolding World Wide Web epoch, connected in particular to this era's exceptionally efficient behavior modification, are compared with earlier epochs.